2000
DOI: 10.1074/jbc.m004852200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Protein-tyrosine Phosphatase 1B as the Major Tyrosine Phosphatase Activity Capable of Dephosphorylating and Activating c-Src in Several Human Breast Cancer Cell Lines

Abstract: c-Src tyrosine kinase activity is elevated in several types of human cancer, and this has been attributed to elevated c-Src expression levels, increased c-Src specific activity, and activating mutations in c-Src. We have found a number of human breast cancer cell lines with elevated c-Src specific activity that also possess elevated phosphatase activity directed against the carboxyl-terminal negative regulatory domain of Src family kinases. To identify this phosphatase, cell extracts from MDA-MB-435S cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
216
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(230 citation statements)
references
References 60 publications
11
216
2
1
Order By: Relevance
“…Pretreatment with PAO, an inhibitor of tyrosine phosphatases, resulted in a marked decrease in basal SRC activity, suggesting that the endogenous tyrosine phosphatases may represent one of the mechanisms that maintain the basal activity of SRC, probably by dephosphorylating Tyr-530 of SRC (10). Indeed, elevated SRC activity in several cancer cell lines correlates with enhanced tyrosine phosphatase activity in these cell lines (26,27), whereas hyperphosphorylation of this residue occurs in cells deficient of tyrosine phosphatase-B, and reduced SRC activity is observed in cells deficient in protein-tyrosine phosphatase-␣ (28, 29). Interestingly, this study showed that specific inhibition of the protein expression of SHP-2 had no effect on the basal activity of SRC in these ECs, suggesting a role for phos- phatases other than SHP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with PAO, an inhibitor of tyrosine phosphatases, resulted in a marked decrease in basal SRC activity, suggesting that the endogenous tyrosine phosphatases may represent one of the mechanisms that maintain the basal activity of SRC, probably by dephosphorylating Tyr-530 of SRC (10). Indeed, elevated SRC activity in several cancer cell lines correlates with enhanced tyrosine phosphatase activity in these cell lines (26,27), whereas hyperphosphorylation of this residue occurs in cells deficient of tyrosine phosphatase-B, and reduced SRC activity is observed in cells deficient in protein-tyrosine phosphatase-␣ (28, 29). Interestingly, this study showed that specific inhibition of the protein expression of SHP-2 had no effect on the basal activity of SRC in these ECs, suggesting a role for phos- phatases other than SHP-2.…”
Section: Discussionmentioning
confidence: 99%
“…PTP1B was also co-immunoprecipitated with b1 integrin and colocalized with integrins at focal adhesions (Arregui et al, 1998). PTP1B has also been purified and identified from breast cancer cells as a phosphatase that could dephosphorylate a peptide containing phosphotyrosine 527 (Bjorge et al, 2000). It has been well described that a third tyrosine phosphatase, Shp2, plays a role in integrin signaling.…”
Section: Dephosphorylation Of Src Y527mentioning
confidence: 99%
“…Interaction with focal adhesion complexes is most likely through interaction with p130 cas and is mediated by a proline rich, SH3-binding domain in PTP1B (Liu et al, 1996). The role of PTP1B in focal adhesion complexes appears to be activation of Src Bjorge et al, 2000) and failure to activate Src leads to impaired integrin-mediated adhesion and signaling . Even though Fig.…”
Section: Maintaining Stable Adhesions: the Nonreceptor Tyrosine Kinasmentioning
confidence: 99%